Chloroplast pigments and photochemical efficiency of West Indian cherry under salt stress and potassium-phosphorus fertilization - Dias, Adaan Sudario; Lima, Geovani Soares de; Gheyi, Hans Raj; Furtado, Guilherme de Freitas; Soares, Lauriane Almeida dos Anjos; Nobre, Reginaldo Gomes; Moreira, Rômulo Carantino Lucena; Fernandes, Pedro Dantas (Semina: Ciências Agrárias, 2021)
The objective of this study was to evaluate chloroplast pigments and photochemical efficiency of West Indian cherry cv. BRS 366 Jaburu as a function of irrigation water salinity and potassium-phosphorus fertilization combinations in the second year of cultivation. The experiment was carried out in a protected environment in Campina Grande, Brazil. Treatments were distributed in randomized blocks, in a 5 Ã— 4 factorial scheme, corresponding to five levels of electrical conductivity of irrigation water ECw (0.6, 1.4, 2.2, 3.0 and 3.8 dS m-1) and four combinations of potassium-phosphorus fertilization (100/100, 85/85, 60/60 and 45/45% of the K2O/P2O5 recommendation for the second year of cultivation 200 g of K2O and 120 g of P2O5 per plant per year) with three replicates. Irrigation with saline waters hampered the biosynthesis of chloroplast pigments and the photochemical efficiency of West Indian cherry cv. BRS 366 Jaburu in the second year of cultivation. Water salinity from 2.6 dS m-1 reduced the maximum fluorescence, variable fluorescence, and quantum efficiency of photosystem II of West Indian cherry plants cv. BRS 366 Jaburu. Fertilization with 60/60 and 85/85% of the K2O/P2O5 recommendation promotes an increase in the synthesis of chlorophylls a and b, respectively, in the first and second production cycles of the second year of cultivation. Supply of 85/85% of the K2O/P2O5 recommendation promoted an increase in maximum and variable fluorescence in plants subjected to water salinities of 0.6, 2.2, and 3.8 dS m-1 in the second cycle and reduced the initial fluorescence, regardless of the salinity level in the first and second production cycles of West Indian cherry.